1997
DOI: 10.1007/bf02726124
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cerebral palsy

Abstract: Cerebral palsy is a major cause of crippling in children, but it's etiology is poorly understood. This case control study was done to assess some of the identified risk factors for cerebral palsy, 125 cerebral palsy cases selected from hospital clinic and 125 age and sex matched neighbourhood controls, all aged less than 5 years and residing in Delhi (India) were studied. Information regarding antenatal, natal and postnatal period was collected by mother's interview, and wherever available, from hospital recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
25
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 28 publications
4
25
2
Order By: Relevance
“…10,12,15 The next most common post-natal factor observed was meconium aspiration syndrome (MAS) in 6 (13.04%) patients and icterus neonatorum in 6 (13.04%) patients, maximum being observed in patients with spastic quadriplegia, on the contrary, higher proportion of icterus among patients of CP was reported by Kapoor et al, Dale and Stanley and Pharoah et al reported higher proportion of icterus among patients of CP. 6,7,12,19 Intracranial hemorrhage and neonatal septicemia were observed as risk factors in 5 (10.86%) patients each. Grether et al, and others observed both were significantly associated with increased risk of developing CP.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…10,12,15 The next most common post-natal factor observed was meconium aspiration syndrome (MAS) in 6 (13.04%) patients and icterus neonatorum in 6 (13.04%) patients, maximum being observed in patients with spastic quadriplegia, on the contrary, higher proportion of icterus among patients of CP was reported by Kapoor et al, Dale and Stanley and Pharoah et al reported higher proportion of icterus among patients of CP. 6,7,12,19 Intracranial hemorrhage and neonatal septicemia were observed as risk factors in 5 (10.86%) patients each. Grether et al, and others observed both were significantly associated with increased risk of developing CP.…”
Section: Discussionmentioning
confidence: 95%
“…As Kapoor et al and others also found no association with the parental age. 6,7,10,12 As per their living area no specific pattern of CP with rural 27(58.69%) or urban 19 (41.31%) background was found in review of literature.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…15 Studies of clinic attendees in these settings have reported high rates of spasticity similar to that in high-resource countries, from 70% to 90%. 14,[16][17][18][19][20] Studies have tended to identify higher rates of quadriplegia than those reported in the west (60% to 86%), 16,17,20 although the only population-based study found a high rate of spastic diplegia (72.9%). 14 Differences in prevalence and motor patterns between high-and low-resource countries reported in the literature remain unclear; however, the etiology has been reported to differ markedly.…”
mentioning
confidence: 99%
“…12 In low-resource countries there is poor survival of preterm infants, and home deliveries by unskilled birth attendants continue to dominate. 17 Birth asphyxia and low birth weight are reported as the prevailing causes of CP in low-resource countries, 16,17 along with kernicterus and postnatal causes such as meningitis and cerebral malaria. 3,14 The motor outcomes of children in highresource countries have been well described based on their level of gross motor function (Gross Motor Function Classification System [GMFCS]).…”
mentioning
confidence: 99%